2020
DOI: 10.1177/1534734620938988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Collagen Granule Dressing Versus Conventional Dressing in Patients With Diabetic Foot Ulcer

Abstract: Background. Diabetic foot ulcer (DFU) is a difficult, chronic wound with a significant long-term influence on the morbidity, mortality, and quality of life of patients. There is much information about the biochemical features of collagen and its function in wound healing. The aim of this study was to compare the results of DFU patients treated with and without collagen. Methods. A retrospective evaluation was made of the data of patients with DFU who underwent collagen treatment and physiological serum (PS) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some previous works have reported the collagen electrospinning process. These works described the use of toxic, organic solvents, such as 1,1,1,3,3,3‐hexafluoro‐2‐propanol (HFIP), and recently, the use of the acetic acid aqueous solution, a green solvent 31–33 . However, the maintenance of the natural triple helical structure that forms collagen fibrils makes the electrospinning process a challenge for tissue engineering 34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous works have reported the collagen electrospinning process. These works described the use of toxic, organic solvents, such as 1,1,1,3,3,3‐hexafluoro‐2‐propanol (HFIP), and recently, the use of the acetic acid aqueous solution, a green solvent 31–33 . However, the maintenance of the natural triple helical structure that forms collagen fibrils makes the electrospinning process a challenge for tissue engineering 34 .…”
Section: Introductionmentioning
confidence: 99%
“…These works described the use of toxic, organic solvents, such as 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), and recently, the use of the acetic acid aqueous solution, a green solvent. [31][32][33] However, the maintenance of the natural triple helical structure that forms collagen fibrils makes the electrospinning process a challenge for tissue engineering. 34 This structure, which is characteristic of type I collagen, showed degradation during electrospinning process that is attributed to the solvents.…”
mentioning
confidence: 99%
“…In Nigeria, Anumah et al 10 have demonstrated that education is an inexpensive and effective approach towards prevention of lower-limb amputations. Colak et al 11 have compared collagen granule dressings with conventional dressings in patients with DFUs, showing the benefits of the former. In 3 UK centres, Lim et al 12 have looked at the real-world experience with VACOped boot for DFUs management.…”
Section: Editorialmentioning
confidence: 99%
“…But the healing was better with the rapid start of granulation tissue formation and wound closure in wounds of less than six months' duration treated with collagen dressings. In addition, patients with collagen covering experienced a reduction in pain and a reduction in bacterial colonization in the wound.The results of the study by C o l a k et al[6] demonstrated that collagen dressings are better than conventional dressings with regard to early granulation tissue and shorter hospital stay. The aim of this study was to compare the results of diabetic foot ulcer patients treated with and without collagen.…”
mentioning
confidence: 99%